2019
DOI: 10.3390/sym11030350
|View full text |Cite
|
Sign up to set email alerts
|

Application of MCDM Methods in Sustainability Engineering: A Literature Review 2008–2018

Abstract: Sustainability is one of the main challenges of the recent decades. In this regard, several prior studies have used different techniques and approaches for solving this problem in the field of sustainability engineering. Multiple criteria decision making (MCDM) is an important technique that presents a systematic approach for helping decisionmakers in this field. The main goal of this paper is to review the literature concerning the application of MCDM methods in the field of sustainable engineering. The Web o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
136
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(140 citation statements)
references
References 137 publications
2
136
0
2
Order By: Relevance
“…Inti et al [42] presented a modified AHP model, the characteristics of the additive transitivity of fuzzy relationships. Stojčić et al [43] identified 108 articles in the period 2008-2018 relating to the issue of sustainable engineering (23 specific articles in the transport and logistics sector). The results of this document show that sustainable engineering is an area that is quite suitable for the use of multi-criteria decision methods (MCDM).…”
Section: Introductionmentioning
confidence: 99%
“…Inti et al [42] presented a modified AHP model, the characteristics of the additive transitivity of fuzzy relationships. Stojčić et al [43] identified 108 articles in the period 2008-2018 relating to the issue of sustainable engineering (23 specific articles in the transport and logistics sector). The results of this document show that sustainable engineering is an area that is quite suitable for the use of multi-criteria decision methods (MCDM).…”
Section: Introductionmentioning
confidence: 99%
“…The WASPAS-SVNS extension of the WASPAS method is used to solve the mentioned MCDM problem. Previously, the WASPAS-SVNS method was applied for the problem of the real world [17,20,21,48]. The basis of this method is governed by the single-valued neutrosophic set.…”
Section: Mcdm Waspas Methodsmentioning
confidence: 99%
“…Therefore, the selection of the edge detection algorithm for the particular image can be accomplished using multi-criteria decision-making (MCDM) methodology. MCDM is an important technique that is used in sustainability engineering [17], as it is applied in a variety of areas: an improvement of image segmentation [18] and edge detection algorithms [7], sustainable urban development [19], ranking of the urban parks according to their safety [20], environment exploration by autonomous mobile robots [21], concentrated solar power (CSP) [22,23], combine heat and power (CHP) [24]. However, the multi-criteria analysis is not widely applied for the selection of the edge detection methods for application-specific images based on their features.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Stević et al [24] introduced the measurement of alternatives and ranking according to compromise solution (MARCOS) method for sustainable supplier selection in healthcare industries. Introducing new extensions to existing multicriteria decision-making models such as the extended TOPSIS method by Yu et al [25] are also gaining popularity for solving specific sustainability problems [26][27][28]. Furthermore, there are integrated approaches that include multiple MCDM techniques to deal with such problems; for example, the integrated grey based multicriteria decision-making approach for the evaluation of renewable energy sources developed by Çelikbilek and Tüysüz [29].…”
Section: Prosmentioning
confidence: 99%